Pemetaan spasio-temporal ikan-ikan herbivora di Kepulauan Spermonde, Sulawesi Selatan [Spatio-temporal mapping of herbivorous fishes at Spermonde Islands, South Sulawesi] - Ahmad Faizal; Jamaluddin Jompa; Natsir Nessa; Chair Rani (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2012)
Herbivorous fish is one of the indicators of coral reef ecosystem health. The healthiness of coral reef ecosystem is characterized by the increasing of herbivorous fish abundance. The aims of this study were to map the spatio-temporal distribution of herbivorous fish and relationship between the health condition of coral reef and herbivorous fishes. The number of species and density of herbivorous fish were enumerated using visual census technique, whereas the assessment of coral reef condition using the quadrant methods. The distribution of data was plotted using data mapping technique. The density of herbivorous fishes between islands was compared using analyses of variance (ANOVA). Relationship between the density of fishes and coral reef was analyzed using simple linear regression. The results showed that abundance of herbivorous fish was range 0.014-0.532 ind.m-2 (April-August periods) and analysis of variance revealed that the abundance of herbivorous fish species between islands was different significantly. The density of herbivorous fish was correlated positively with coral reef condition. Abstrak Ikan herbivora di terumbu karang menjadi salah satu indikator tingkat kesehatan ekosistem. Pada terumbu karang yang sehat biasanya ditandai dengan kelimpahan ikan herbivora yang tinggi. Penelitian ini bertujuan untuk memetakan distribusi spasial dan temporal ikan herbivora dalam kaitannya dengan kondisi kesehatan karang. Pendataan jumlah jenis dan kepadatan ikan herbivora dengan metode transek sabuk dan pencacahan dengan teknik visual sensus, sedangkan penilaian kesehatan karang dengan metode transek kuadran. Data sebaran diplot dengan teknik pemetaan sedangkan data kepadatan dikelompokkan berdasarkan pulau dan dianalisis perbedaannya dengan analisis ragam. Hubungan antara kepadatan ikan herbivora dengan kesehatan karang dilakukan dengan menggunakan regresi sederhana. Hasil penelitian menunjukkan rata-rata kepadatan ikan herbivora periode April-Agustus dengan kisaran 0,014-0,532 ekor.m-2. Hasil analisis ragam menunjukkan bahwa ada perbedaan kepadatan ikan herbivora antarpulau. Hubungan antara kepadatan ikan herbivora dengan kondisi kesehatan karang berkorelasi positif dan nyata.